2001
DOI: 10.1034/j.1600-0609.2001.067001030.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between deferoxamine and deferiprone (L1) in iron‐loaded thalassemia patients

Abstract: L1 had comparable efficacy as deferoxamine with minimal side effects and better compliance. Provided long term side effects are not encountered, L1 seems to be a valuable alternative iron chelator for patients unable or unwilling to use deferoxamine effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
32
1
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 23 publications
7
32
1
2
Order By: Relevance
“…Results of randomized clinical trials comparing DFO with DFP demonstrated no difference after 12 months of treatment in serum ferritin levels or liver iron concentration [23,24]. Similar results have been obtained in other studies [25,26,27]. …”
Section: Dfp Efficacysupporting
confidence: 76%
“…Results of randomized clinical trials comparing DFO with DFP demonstrated no difference after 12 months of treatment in serum ferritin levels or liver iron concentration [23,24]. Similar results have been obtained in other studies [25,26,27]. …”
Section: Dfp Efficacysupporting
confidence: 76%
“…61 Patients receiving DFP, or DFP with DFO, showed a reduction in SF over time greater than patients who received DFO alone in two trials. 57,58 Three studies were analyzed for the comparison of DFX with DFO in severely iron loaded patients 9,11,43 ( Table 4). Altogether, 335 patients received DFX and 256 received DFO.…”
Section: Switching To An Alternative Iron Chelation Therapy In Patienmentioning
confidence: 99%
“…5,8 More cardiac events occurred while on DFO, and the analysis of cardiac disease free survival over the 5-year period was significantly more favorable in the DFP group. 8 LIC was measured at baseline and at the end of the trial in one study, 60 and SF in six, 8,[57][58][59][60][61] There was no significant difference in pre-and post-study LIC between patients using combined therapy and patients using DFO alone. 61 Patients receiving DFP, or DFP with DFO, showed a reduction in SF over time greater than patients who received DFO alone in two trials.…”
Section: Switching To An Alternative Iron Chelation Therapy In Patienmentioning
confidence: 99%
See 1 more Smart Citation
“…As opposed to deferoxamine, which must be administered by subcutaneous infusion, the oral formulation of deferiprone simplifies treatment, improves patients' quality of life, and improves adherence (Tricta et al, 1996;Franchini and Veneri, 2004;Delea et al, 2007). Although the long-term safety profile of deferiprone is well defined, the mechanism of and factors involved in its adverse effects, such as gastrointestinal disturbances, arthralgia, neutropenia, and agranulocytosis, are unclear (Agarwal et al, 1990;Taher et al, 2001;Ceci et al, 2002;Cohen et al, 2003;Franchini and Veneri, 2004), thus emphasizing the need to decipher the underlying mechanisms and factors involved in these adverse effects. Deferiprone has good bioavailability, but its clearance is accelerated by rapid biotransformation: approximately 85% of the drug is metabolized to a nonchelating (inactive) 3-O-glucuronide conjugate (Huang et al, 2006) by UDP-glucuronosyltransferases (UGTs).…”
mentioning
confidence: 99%